RESPON DAN KESIAPAN GURU PENDIDIKAN AGAMA ISLAM TERHADAP PEMBERLAKUAN KURIKULUM 2013 MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 5 YOGYAKARTA - Puput Rahmat Saputra (Jurnal Pendidikan Agama Islam, 2013)
The national education goals have not been achieved because of depraved morality and education materials that emphasize cognitive, and affective aspects of the exclusion of the curriculum psikomotorik. Curriculum inovation will be a solution to the problems by launching a new curriculum. This research was conducted to determine the responses and readiness of Islamic education teachers curriculum in 2013 on Islamic Education.This research is qualitative. The subjects of this research were Islamic Education teachers of class VII. Data collection is done by conducting observations, in-depth interviews, and the data documentation. Then the data were analyzed by giving meaning to the data collected, and the conclusions drawn from the meaning that is to prepare the work for responses and the readiness of Islamic education teachers in SMP N 5 Yogyakarta. The data were validated by using a triangulation technique and the extension of participation in the study.The results showed: 1) the implementation of the 2013 curriculum of Islamic Education in SMP N 5 Yogyakarta otherwise has been running well. 2) the response of Islamic education teacher class VII as one of the teachers who is implementing Curriculum 2013 is very supportive, 3) the readiness of PAI teachers at SMP N 5 Yogyakarta on the use of the curriculum in 2013 which consisted of professional readiness, and teacher pedagogical readiness against the imposition of Islamic education curriculum in 2013 declared ready.